Activation Mechanism of LRRK2 and Its Cellular Functions in Parkinson’s Disease - Katharina E. Rosenbusch; Arjan Kortholt (Parkinson's Disease)
Human LRRK2 (Leucine-Rich Repeat Kinase 2) has been associated with both familial and idiopathic Parkinson’s disease (PD). Although several LRRK2 mediated pathways and interaction partners have been identified, the cellular functions of LRRK2 and LRRK2 mediated progression of PD are still only partially understood. LRRK2 belongs to the group of Roco proteins which are characterized by the presence of a Ras-like G-domain (Roc), a C-terminal of Roc domain (COR), a kinase, and several protein-protein interaction domains. Roco proteins exhibit a complex activation mechanism involving intramolecular signaling, dimerization, and substrate/effector binding. Importantly, PD mutations in LRRK2 have been linked to a decreased GTPase and impaired kinase activity, thus providing putative therapeutic targets. To fully explore these potential targets it will be crucial to understand the function and identify the pathways responsible for LRRK2-linked PD. Here, we review the recent progress in elucidating the complex LRRK2 activation mechanism, describe the accumulating evidence that link LRRK2-mediated PD to mitochondrial dysfunction and aberrant autophagy, and discuss possible ways for therapeutically targeting LRRK2.